2013
DOI: 10.1177/1941738113486077
|View full text |Cite
|
Sign up to set email alerts
|

Common Dental Injury Management in Athletes

Abstract: Context:Orofacial and dental trauma continues to be a commonly encountered issue for the sports medicine team. All sports have some risk for dental injury, but “contact sports” presumably incur more risk. Immediate evaluation and proper management of the most common injuries to dentition can result in saving or restoration of tooth structure. Despite the growing body of evidence, mouth guard use and dental protection have not paralleled the increase in sports participation.Evidence Acquisition:A PubMed search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
(93 reference statements)
0
33
0
6
Order By: Relevance
“…Third, our questionnaire did not include a query about the use of mouthguards. Although mouthguards markedly reduce the incidence of sports-related dental injuries among athletes [ 12 , 14 17 ], the use of mouthguards, especially among young athletes, probably depends on the coaching quality. Since the prevalence of sports-related dental injuries remains high (more than one-eighth of young athletes), there must be other strategies for the prevention of sports-related dental injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, our questionnaire did not include a query about the use of mouthguards. Although mouthguards markedly reduce the incidence of sports-related dental injuries among athletes [ 12 , 14 17 ], the use of mouthguards, especially among young athletes, probably depends on the coaching quality. Since the prevalence of sports-related dental injuries remains high (more than one-eighth of young athletes), there must be other strategies for the prevention of sports-related dental injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Sports experts including dentists recommend that mouthguards be worn to prevent sports-related dental injuries. Mouthguards markedly reduce the incidence of sports-related dental injuries among athletes, especially those playing full-contact sports such as rugby and football [ 12 , 14 17 ]. However, because the wearing of mouthguards is not mandatory for young athletes participating in sports with less contact [ 12 , 17 , 18 ], the prevalence of sports-related dental injuries remains high [ 11 , 12 , 14 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basketball, football, hockey, martial arts, and boxing carry the highest risk of dental injuries [1]. Thus, the use of mouthguards during sports is a commonly encouraged procedure by dental surgeons and sports technicians [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown how traumatic dento-alveolar injuries progressed over time in a group of 30 young athletes aged between 8 and 20. Recovery time in sports after an injury to the body is a much debated subject in the relevant literature [ 31 ], but there is an evident lack of studies on the recovery time needed after traumas affecting mouth and teeth [ 32 ], and consequently a lack of protocols and procedures to follow in such cases [ 10 ].…”
Section: Discussionmentioning
confidence: 99%